SYSTEMATIC POSITION OF THE SCIAENID CORVINA CAROUNA CUVIER 1830 - Lalmohan, R S (Indian Journal of Fisheries, 2011)
Cuvier (1830) described Corvina carouna based on the specimens collectedby Mr. Dussumier from the Malabar coast. Later, Day (1878) and Weberand de Beaufort (1936) synonymised it with Johinus carutta. Trewavas (1977)has considered it to be the synonym of Corvina belangeri Cuvier 1830, a specieswhich has many common characters of Johnius carouna (Cuvier). But whenthe type specimen of Corvina carouna Cuvier from Museum Nationale d' HistoireNaturelle, Paris, was examined, it was found to be a valid species, occurringcommonly in the Cochin backwaters and estuaries